Community directed assessment of pain in a northern Saskatchewan Cree community - Tayah Zhang; Elder Rose Dorian; Sally Sewap; Rachel Johnson; Heather Foulds; Brenna Bath; Stacey Lovo (International Journal of Circumpolar Health, 2024)
Indigenous Elder advisors in Pelican Narrows, a Cree community in Northern Saskatchewan, have indicated that Western pain scales may not be responsive tools for pain assessments within their community. This study employed a mixed methods research design that involved two phases. Phase one was the development of a pain scale in collaboration with an Elder and a Knowledge Keeper. Phase two was a pilot of the CDPS utilised during virtual physiotherapy sessions for chronic back pain. Twenty-seven participants completed the pre-physiotherapy treatment questionnaires, and 10 participants engaged in semi-structured interviews (9 community members; 1 healthcare provider). A weighted kappa analysis yielded k = 0.696, indicating a good agreement between the CDPS and Faces Pain Scale-Revised in terms of documenting participants’ pain. Qualitative data from interviews with community members revealed three major themes: 1) Learnings Regarding Pain Scales, 2) Patient Centered Care; and 3) Strength-Based Solutions for Improving Pain Communication. Two themes were uncovered through conversations with the HCP: 1) Perspectives on CDPS and 2) Healthcare Provider Experiences Communicating about Pain. Moreover, a patient-centredcentred approach is important to ensure comprehensive pain assessments.